Fundamentals of marketing - Stanton, William J.; Miller, Kenneth E.; Layton, Roger A. (Sydney : McGraw-Hill, 1994)
Modern marketing and its environment. Target markets. The product. The price. Distribution. Promotion. Marketing in special fields. Managing the marketing effort.
Keywords: Marketing; Management; Marketing; Marketing -- Case studies; Marketing -- Australia -- Case studies